Influence of Tetrabromobisphenol-A on the Fate and Behavior of Zinc Oxide Nanoparticles Affected by Salts, Humic Acid, and Bovine Serum Albumin in Water Systems - Anwar Ul Haq Khan; Yanju Liu; Ravi Naidu; Cheng Fang; Ho Kyong Shon (Toxics)
The environmental release of zinc oxide nanoparticles (ZnO-NPs) may have consequences for ecosystems. The behavior and environmental effects of ZnO-NPs could change due to their interactions with other existing substances. This research explored how the presence of coexisting organic pollutants (like tetrabromobisphenol-A (TBBPA)), electrolytes (such as NaCl and CaCl2), natural organic materials (including humic acid (HA)), and bovine serum albumin (BSA) in simulated water affected the behavior of ZnO-NPs. Various characterization techniques were used to analyze the size, shape, purity, crystallinity, and surface charge of ZnO-NPs following interactions (after one day, one week, two weeks, and three weeks) at pH 7. The findings demonstrated changes in both the size and zeta potential of the ZnO-NPs in isolation and when TBBPA and electrolytes were included in the suspension. The size and surface charge exhibited different variations across fixed concentrations (5 mM) of various electrolytes. HA and BSA contributed to the dispersion of ZnO-NPs by affecting the zeta potential. These dispersion effects were also observed in the presence of TBBPA and salts, attributed to their substantial aliphatic carbon content and complex structures. Potential interaction forces that could explain the adsorption of TBBPA include cation bridging, hydrophobic interactions, hydrogen bonding, electrostatic interactions, and van der Waals forces. The co-occurrence of organic pollutants (TBBPA) and natural organic compounds (HA and BSA) can alter the surface properties and behavior of ZnO-NPs in natural and seawater, aiding in the understanding of the fate and impact of engineered nanoparticles (such as ZnO-NPs) in the environment.